ANALYSIS OF FACTORS AFFECTING GRDP IN THE AGRICULTURAL SECTOR IN EAST JAVA PROVINCE - Dhea Amelia Putri Kamila; Sishadiyati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
East Java Province is a province that is one of the largest agricultural commodity producing areas in Indonesia. The agriculture, forestry and fisheries sectors are sectors that drive economic growth in East Java because they have contributed greatly and provided supporting capacity for other sectors. The number of agricultural sector workers in East Java Province is the highest in Indonesia, however, with this high workforce, the GDP of the agricultural sector in East Java experiences a slow increase every year. The decline in the area of ​​rice fields and the rise and fall of domestic investment (PMDN) in the agricultural sector can also affect the value of GRDP growth in the agricultural sector in East Java. This research aims to determine the influence of agricultural sector labor, rice field area, domestic investment (PMDN) in the agricultural sector on GRDP in the agricultural sector in East Java Province. This research uses a quantitative method using secondary data from 2002 to 2022. The method used is multiple linear regression analysis using the SPSS 23 application. The results of this research show that agricultural sector labor has a significant negative influence on the agricultural sector's GRDP while the area paddy fields and domestic investment have no influence on the GDP of the agricultural sector. However, simultaneously the workforce in the agricultural sector, the area of ​​rice fields, domestic investment influence the GRDP in the agricultural sector of East Java Province.